Immune System Sex Differences May Bridge the Gap Between Sex and Gender in Fibromyalgia - Meester, Irene; Rivera-Silva, Gerardo Francisco; González-Salazar, Francisco (Frontiers in Neuroscience, 2020)
The fibromyalgia syndrome (FMS) is characterized by chronic widespread pain, sleep disturbances, fatigue, and cognitive alterations. A limited efficacy of targeted treatment and a high FMS prevalence (2-5% of the adult population) sums up to high morbidity. Although, altered nociception has been explained with the central sensitization hypothesis, which may occur after neuropathy, its molecular mechanism is not understood. The marked female predominance among FMS patients is often attributed to a psychosocial predisposition of the female gender, but here we will focus on sex differences sexual dimorphism in neurobiological processes, specifically those of the immune system, as various immunological biomarkers are altered in FMS. The activation of innate immune sensors is compatible with a neuropathy or virus-induced autoimmune diseases. Considering sex differences in the immune system and the clustering of FMS with autoimmune diseases, we hypothesize that the female predominance in FMS is due to a neuropathy-induced autoimmune pathophysiology. We invite the scientific community to verify the autoimmune hypothesis for FMS.